Clinical Utility Of The Exhaled Nitric Oxide (NO) Measurement With Portable Devices In The Management Of Allergic Airway Inflammation And Asthma - Duong-Quy, Sy (J Asthma Allergy, 2019)
Nitric oxide (NO) is a potential bioactive gas produced continuously and constantly in the airways of healthy subjects. In allergic airway inflammation, the level of exhaled NO is usually increased and mediated by inducible nitric oxide synthase (iNOS) enzyme presenting in the epithelium and different inflammatory cells. The measurement of NO concentration in the airway is possible with portable devices which use an electroluminescence technique. In subjects with upper airway with allergic inflammation such as in allergic rhinitis, the measurement of nasal NO (nNO) may help to diagnose and manage the disease. In the lower airway, increased fractional exhaled NO (FENO) reflects directly the inflammatory process that occurs in the airways that are typically seen in asthma. It has been shown that there is a strong correlation between FENO levels and increased activity of airway inflammation mediated by immuno-allergic cells and mediators. Thus, FENO has higher specificity and sensitivity than other methods in diagnosing the severity of inflammation in asthmatic patients. Moreover, the correlation between increased FENO levels and a high risk of bronchial hyperresponsiveness has also been demonstrated. FENO is also a relevant biomarker to evaluate asthma status due to the change of its values occurring earlier than clinical manifestations and spirometry parameters. In addition, the measurement of FENO with portable devices helps to support the diagnosis of asthma, to follow-up the control of asthma and to personalize asthmatic patients for target treatment with biologic therapy. Therefore, measuring FENO with portable devices in the diagnosis and treatment of allergic airway inflammation, especially in asthma, is one of the most essential applications of NO biomarkers in exhaled breath.